Pengaruh Penerimaan Pajak Daerah Terhadap Peningkatan Pad DKI Jakarta Periode 2012-2019 (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to find out the effect of local taxes on increasing DKI Jakarta tax revenue. Sample was selected using purposive sampling method and valid data which was taken from Realization of Local Tax and Local Revenue Report of DKI Jakarta Period 2012-2019. Data processing thecnique using descriptive test, classic assumption test and multiple regression analysis which helped by SPSS Program for windows released 23. The result of this study indicate the hotel taxes have negative effect and not significant on increasing of local revenue. Restaurant taxes have positive effect and significant on the increasing local revenue, and advertising taxes have positive effect and not significant on the increasing of local revenue. The implication of this study is the need to socialize and maximize local taxes collection.